Young athlete major event experiences: brand co-creators and ambassadors. Issue 3 (4th March 2017) - MacIntosh, Eric
Abstract: Youth sport events have become rather recent line extensions within some of the world's largest sport event properties such as the Commonwealth Games Federation (CGF). This paper draws on feedback from 184 young athletes regarding their experiences during the 2011 Commonwealth Youth Games (CYG) in the Isle of Man. The athlete perspective is considered in lieu of some of the stated brand promises of the CGF. Athlete feedback demonstrated that the CYG acts as a conduit to protect important aspects of the brand while adding further potential to enhance other brand assets. Consequently, for the property rights holders to raise the level of quality for youth athletes in particular, management must recognize the value in their feedback and opinion and consider them important co-creators of the brand.